IMPACT OF STAFF TRAINING AND DEVELOPMENT PRACTICES ON ORGANIZATIONAL PERFORMANCE OF PUBLIC INSTITUTIONS IN RWANDA - Rukumba, Steven; Mukulira, Dr. Olivier (Journal of Human Resource and Leadership, 2017)
Purpose: Over time, organizations have been embarking on training and capacity building for their employees so as to enhance productivity and overall performance of the organizations. The overall objective of this study was to investigate the impact of staff training and development practices on organizational performance of Rwanda Revenue Authority. The literature review focused on data relating staff training and development, organizational performance, critical literature and conceptual framework. Methodology: Data were collected from primary and secondary sources by means of questionnaire and documentary analysis. The collected data were presented in tables, analysed and arranged in form of percentage and frequency distribution and interpretation thereon. To ensure reliability, alternative form method was used while expert panel model were used to ensure validity of instruments. Results: It was found that public institutions put in place training and development program. In this angle Rwanda Revenue Authority (RRA) uses different techniques of staff training and development whereby Task or job analysis is the most technique used, as per 82% of the respondents. The results showed that RRA very frequently trains its staff as shown by 67.6% of the respondents whereby it mainly uses "on the job training/induction" method as per 68% of respondents. On average (4.143), the respondents were content with the role played by and benefits derived from training and developments being the improved productivity, developed self-confidence and positive attitude towards better service, etc. Due to training and development practices, the organization has improved its overall productivity (as per the majority of the respondents, 93.8), costs and wastage and the alike have reduced. The short period accorded to training and development, lack of providing training materials to serve as future reference were found to be most challenges facing this act. Policy recommendation: It was recommended to RRA to revise on the period allocated to the training, recruit highly skilled trainers and to the workers (trainees) of RRA to develop the sense of self training.